Determinants of Graduate Youth Unemployment - Gebisa, Diriba Ayele; Etana, Negash Geleta (Faculty of Islamic Economics and Business of Institut Agama Islam Negeri (IAIN) Pekalongan, 2019)
Today, youth unemployment is a common agenda and a critical issue of all countries; particularly in developing countries. In Ethiopia, lack of employment opportunities for educated young people is a critical development challenges facing the country. The objective of this study was to identify the determinants of graduate youth unemployment. To answer the research objective data was collected by a structured questionnaire from 312 samples of respondents, wherein a snow ball sampling technique was used and data was analyzed using mixed research design, descriptive and casual design; where a binary logistic regression model used to examine the relationship between dependent and independent variables. The result indicated that amongst the nine variables of the determinants of graduate youth unemployment; education, number of graduates, work experience, career advice, market information, family income, aspire to the low-income job, and education quality, all were significantly affected unemployment rate except entrepreneurial ability. As a result, based on these findings, it can be recommended that there is a critical need for government, NGOs and all other stakeholders to work on these determinants to reduce graduate unemployment.